Practical PAS doctores sociological investigation results on projecting regional pathoanatomical centers prospects - Rosha, L. G. (Journal of Education, Health and Sport, 2018)
The purpose - to study the doctors working in pathoanatomycal service (PAS) assessment on the project of Regional Pathoanatomycal Center (RPAC) prospects. Materials and methods. According to a specially formulated questionnaire, 53 doctors were interviewed. Statistical processing of the obtained results is carried out using generally accepted statistical methods. Results. The estimation of the perspective implementation of the RPAC project is given, taking into account the current state of the PAS. Conclusions. The study results has shown that the modern PAS needs to be reformed.